1969
DOI: 10.1002/hlca.19690520832
|View full text |Cite
|
Sign up to set email alerts
|

La migration de groupes carboxamides lors de la transposition benzilique d'amides α,β‐dicarbonylés. 24e Communication sur les réductones et les composés tricarbonylés‐1,2,3 [1]

Abstract: Under the conditions of the benzilic acid rearrangement, α,β‐diketobutyryl‐di‐phenylamide (Ia) and ‐N‐methylanilide (Ib) are transformed into tartronic acid derivatives (VI), which decarboxylate to lactamides VII. It is proved by 14‐labelling of Ia, that the reaction takes place by carbonamide group migration. The reaction was followed kinetically by polarography at a fixed potential; at low pH the velocity is proportional to [OH⊖], at higher pH it becomes independent of [OH⊖], which is explained by complete t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…If the benzyl group had migrated in the rearrangement, the tracer would have been found in the carboxyl group of 2a* and hence in the released CO,. Thus, the result supports the migration of the CONH, group as observed before in the similar rearrangement reactions [6] [714).…”
Section: *-supporting
confidence: 90%
See 3 more Smart Citations
“…If the benzyl group had migrated in the rearrangement, the tracer would have been found in the carboxyl group of 2a* and hence in the released CO,. Thus, the result supports the migration of the CONH, group as observed before in the similar rearrangement reactions [6] [714).…”
Section: *-supporting
confidence: 90%
“…Kinetics. -In preceding kinetic investigations on rearrangements involving carboxamide-group migrations in the benzil-benzilic acid rearrangement we had found that for N,N-diphenyl-a$-dioxobutyramide [6] the rate of rearrangement is proportional to [OH-], but tends towards a plateau at high pH values; for quinisatine (6) no clear order of dependence of the rearrangement rate upon [OH-] had been found [7]. We have now measured the rate of rearrangement of l a -c at different alkali concentrations; on the same occasion, we have extended the range of our former measurements with 6, for which the course of the rearrangement had been established earlier [7].…”
Section: *-mentioning
confidence: 99%
See 2 more Smart Citations